UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA DI SMPN 1 RANCABUNGUR - Faizah Umami (Jurnal Kinerja, 2023)
The purpose of this study is to analyse the efforts of Islamic Religious Education teachers in improving the religious character of students at SMPN 1 Rancabungur, Bogor district. The research method used is a qualitative method. The technique of collecting data is through interviews, observation, and documentation. The data analysis technique is through the stages of data collection, data reduction, data presentation, verification and confirmation of conclusions. Checking and validating data using source triangulation. The results showed that (a) the efforts of PAI teachers at SMPN 1 Rancabungur, Bogor district in improving the religious character of students that making character development programs through PraKbm activities, providing examples to students, and implementing habituation activities. (b) Supporting factors for Islamic religious education teachers include policies and support from the headmaster as the leader, School facilities and infrastructure that can support character building activities, motivation and support from parents, cooperation of all parties in improving student religious character. (c) The inhibiting factors of Islamic religious education teachers in improving the religious character of students at SMPN 1 Rancabungur are students' backgrounds and lack of student awareness.